Analyzing Gen Z’s Intention to Use Digital Banking: The RolePerceived Usefulness, Attitude, and Perceived Behavioral Control - Rahmadini, Lailly (APPS Publications, 2025)
The purpose of this study is to analyze the factors that influence the behavior of Generation Z in the Jabodetabek region when using digital banking services. In this study, the three primary variables that evaluate perceived usefulness, attitude, and perceived behavioral control. Data collection was conducted through a convenience sampling method, with respondents selected from the Z generation in Jabodetabek. The data that was collected was subsequently analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the SmartPLS4 to evaluate the relationship between the variables. This study has shown that a higher likelihood of intention to use digital banking services is associated with an increase in perceived usefulness, attitude, and perceived behavioral control regarding digital services. The findings of this study offer the banking sector valuable insights for the development of more effective strategies to stimulate the adoption of digital banking among Generation Z, particularly in the Jabodetabek region.